Complexity in the Management of Rural Development Projects: Case of LASESA (Spain) - de los Ríos-Carmenado, Ignacio (2013)
The project and project management complexity has acquired growing interest. This research analyzes the dimensions of complexity in relation to rural development projects and the existing tools for evaluation. We present a novel methodological approach to assess two complementary aspects of project management: (a) the level of complexity of the project, and (b), the effects on behavioral skills. Based on the model Working With People (WWP), the methodology is applied to the Community of Irrigators LASESA in Huesca (Spain), in a rural development project of high complexity, with more than 600 direct beneficiaries involved. Results show how the management of a complex project generates positive effects on the development of behavioral skills of the people involved in the work.